Thematic Approaches to Improve Learning Outcomes Students on a Clean and Healthy Life Theme - Herowati, Nina (Universitas Sebelas Maret, 2020)
The purpose of this research is to improve mastery of learning. One of the approaches used in the learning process is a thematic approach. This research uses classroom action research (PTK). The techniques used were data collection techniques using: (1) observation sheets (teachers and students), (2) test questions then analyzed using a percentage formula. The results of this study indicate that (1) the teacher activity in the first cycle with an average score of 2.91 in the sufficient category and in the second cycle the average score of 4.52 was in the very good category (2) the student activity in the first cycle with an average value of 2.86 was in the sufficient category and in the second cycle got an average value of 4.42 in the very good category. While student learning outcomes in the first cycle with a percentage value of 60.3%, and in the second cycle with a percentage value of 86.7%. Based on the results of the research, it can be concluded that with a thematic approach to the theme of Clean and Healthy Living can improve student learning outcomes in the class of SD NEGERI 02 NEGARADAHA.